Technical standardization work in Leningrad industry (1928–1937) - A. V. Kolobova (Вестник Самарского университета: История, педагогика, филология)
Abstract: The question about the planned nature of the Soviet economy, as well as standard of living of production workers in the late 1920-ies and early 1930-ies remains controversial in science. Despite the fact that the establishment of standards and prices for certain types of work depended on technical regulation, scientists paid little attention to this aspect of organizing the activities of industrial enterprises. However, the required amount of work and the cost of its implementation could not be ignored when drawing up long-term production plans and determining the amount of remuneration. The purpose of the article is to analyze technical standardization work in Leningrad industry in 1928–1937. To achieve the goal, the following tasks were set: to study the organizational and personnel aspects of technical standardization work, to establish the basic methods of standardization used in Leningrad factories and plants, to determine the quality of established standards and to monitor the presence or absence of a relationship between the state of technical standardization work at the enterprise and the implementation of production plans. Using a specific problem method, a systematic approach and structural-functional analysis, the management documentation of production associations and their subordinate enterprises, departments of the secretariat of the Leningrad Regional Committee and the city committee of the All-Union Communist Party of Bolsheviks was studied. As a result, it was concluded that, despite the relationship between the successful implementation of target figures and the quality of technical standardization work, the establishment of standards and prices contributed little to the development of feasible plans and target figures. Technical standardization was used as a tool to solve the financial problems of enterprises and achieve compliance between real and planned indicators.